(3EceGd GdOjf hEJeGe GdfYeI aj EKHGJ GdZjHI hcTa GdMjQIs - (3Gdbej, GHf HGnHnhrjg, CHh LYaQ, GdUOhb, eMeO Hf Ydj Hf GdMSjf Hf ehSi, J (B381 (3gs
(3ChdgG (B:s
... (3ef YPGH Gddg hbO TgOJ Ydjg edGFcI Gddg Chdge hBNQge hcja jYPH UGMH GdfU hbO TgOJ dg edGFcI Gddg cdge hdg hLg BNQ hgh Gf GdbVjI aj GdNdjbI HGbjI Edi jhe GdbjGeI (B...s
(3BNQgG (B:s
...(3bGd PcQ CHh LYaQ eMeO Hf Ydj GdHGbQ Ydjg GdSdGe SjQ GdNdaGA GdGKfj YTQ GdQGTOjf adeG HdZ BNQge bGd (B: (3GdKGfj YTQ GdPj ojUdj YjSi Hf eQje Ydjg GdSdGe Ndag Ydjc HSfJg hGdbQBf GdcQje (B. (3Je GdLRA GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\274s
(3GdCYdGe (B6\274s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds